Examination Of Major Events On The Stock Returns In The KLSE - Cheong, Sum Shau (2004)
This study examines the major events on stock eturns in the Kuala Lumpur Stock Exchange. Specifically, it determines whether the local and international events generate abnormal returns on stock during pre-event, event day , and post-event period. The study identified and examined the top three (3) local events and top five (5) international events of each year from Sin Chew Jit Poh. It covers from the year 1997 until 2002.